New innovations in dementia research: from a new assessment of premorbid functioning to a review of the evidence base for post-diagnostic Cognitive Rehabilitation - Phillips, Joanne (The University of Edinburgh, 2013)
BACKGROUND: Dementia is a national priority for Scotland, and as such, fast and accurate diagnosis plus responsive and well-evidenced interventions post-diagnosis are key. Accurately estimating an individual’s level of premorbid functioning can be a crucial part of establishing that cognitive decline has taken place, enabling clinicians to be more confident and accurate in their diagnosis. Measures that assess premorbid ability should be able to 1) capture current ability in healthy controls and 2) resist the effects of cognitive decline when used in individuals with dementia. At the post-diagnostic stage, there is a growing evidence base for non-pharmacological, tailored interventions for individuals with dementia. However, the evidence base is limited, particularly so for Cognitive Rehabilitation. OBJECTIVES: An empirical study was conducted in order to assess whether a newly developed measure that aims to capture lifelong cognitive reserve (the brain’s ability to withstand pathological change), the Cognitive Reserve Index Questionnaire (CRIq), can capture premorbid ability. Three research questions were addressed; 1) does the CRIq capture current ability in healthy controls? 2) is it resistant to cognitive decline when used with a patient group with dementia? and 3) how does the CRIq compare to a traditional measure of premorbid ability, the NART (National Adult Reading Test)? Another focus of development and innovation in dementia research is that of post-diagnostic interventions. A systematic review was therefore conducted in order to evaluate the effectiveness of Cognitive Rehabilitation for mild-moderate dementia (Alzheimer disease or mixed dementia) in relation to cognitive and functional outcomes. Due to the limited number of RCTs in this field precluding a clear understanding of the evidence base, the additional contribution of non-RCTs was also evaluated. METHOD: For the empirical study N=20 healthy older controls and N=13 patients with dementia were recruited. In order to appropriately address the three research questions both groups were assessed using the NART, the CRIq and the MOCA (Montreal Cognitive Assessment). In addition, the control group were assessed on a measure of current ability, the WAIS-IV Perceptual Reasoning Index. For the systematic review of Cognitive Rehabilitation the CDCIG Specialised Register, ALOIS, was searched in order to identify relevant studies. In addition, previous reviews were searched to identify studies excluded on the basis that they were not an RCT. RESULTS: Results for the empirical study show both CRIq and NART were strongly correlated to current ability (performance on WAIS-IV PRI) in controls, although both significantly overestimated ability. CRIq performance was not affected by the presence of dementia whereas NART predicted premorbid ability was. CRIq and NART showed a different pattern of results between controls and patients, indicating that CRIq may more resistant to the effects of cognitive decline. Ten studies were identified for the systematic review; five RCT and five non-RCT. Study quality was assessed using a well-validated quality assessment tool, and indicated large variability. Eight of the ten studies reported a positive effect of Cognitive Rehabilitation. However, several studies were of poor quality and included aspects of other approaches in their intervention (e.g. Cognitive Training, Cognitive-Behaviour Therapy). CONCLUSIONS: The empirical study found that CRIq over-estimated current ability in controls, but was resistant to cognitive decline in patients. The over-estimation of current ability may be accounted for by the CRIq being normed on an Italian population, thus not reflecting UK cultural norms (e.g. for length of schooling). When the NART and the CRIq were directly compared, the two measures were found to be related, but yet produced significantly different estimates of premorbid ability. This suggests that they may capture different facets of premorbid functioning, with the NART being primarily a verbal performance-based measure, and the CRIq capturing aspects of global cognitive functioning. Clinical implications include the potential utility of the CRIq for patients with language impairment. However the study conclusions are limited by a low N, and therefore have restricted generalisability. In the systematic review, the literature was exhaustively searched and evidence was found for the effectiveness of Cognitive Rehabilitation for mild-moderate Alzheimer disease and mixed dementia. Methodological limitations of the included studies are discussed, and clinical implications are identified. Both the empirical study and the systematic review highlight the need for greater research and development of methods by which dementia care is supported; through more effective methods of diagnosis, to a better evidence base for post-diagnostic interventions.
Keywords: dementia; Alzheimer’s disease; cognitive ability; premorbid ability; cognitive reserve; Cognitive Rehabilitation